PERAN GURU BIMBINGAN DAN KONSELING DALAM PEMBENTUKAN SISWA YANG BERKARAKTER PADA SMKN 1 GLAGAH BANYUWANGI - Galuh Endah Rini; Siti Napisah; Heribertus Wicaksono (Berajah Journal, 2026)
Character formation is a fundamental issue in vocational education because vocational students are prepared to enter the workplace, which requires both technical competence and personal integrity. This study aims to describe the role of Guidance and Counseling teachers in internalizing students’ character values, analyze the implementation of a humanistic approach in counseling services, and identify the supporting and inhibiting factors in character formation at SMKN 1 Glagah Banyuwangi. This research employed a descriptive qualitative approach. Data were collected through observation, interviews, and documentation involving Guidance and Counseling teachers as the main subjects, while students, the principal, the vice principal for student affairs, and productive subject teachers served as significant others. The data were analyzed through data reduction, data display, theme grouping, and conclusion drawing. Research accuracy was strengthened through method, source, data, and theoretical triangulation. The findings reveal that Guidance and Counseling teachers act as companions, developmental facilitators, motivators, mediators, and collaborators. The services include classroom guidance, information services, individual counseling, group counseling, and coordination with school members and parents. The humanistic approach is reflected in empathy, dialogical communication, unconditional acceptance, and a non-judgmental attitude. Students’ character formation becomes more effective when counseling services are supported by school culture, positive relationships, and continuous collaboration.